Dicumyl peroxide as well as preparation method and application thereof
Through the use of composite stabilizer and TiO2-PW catalyst, combined with molecular sieve adsorption and ethanol recrystallization, the purity and stability problems in DCP preparation were solved, high-purity DCP was prepared, and materials such as graphene nanosheets were used in thermally cured inks were used to improve the performance of inks and solve various technical problems of traditional DCP and inks.
Patent Information
- Application Number
- CN202510369342.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The existing DCP preparation technology has problems such as serious equipment corrosion, low product purity, frequent side reactions, unstable reactions, poor safety, single performance of traditional thermally cured inks, uneven dispersion, and limited scope of application.
Compound stabilizers (disodium ethylenediaminetetraacetate and sodium pyrophosphate) are used to inhibit the decomposition of hydrogen peroxide, combined with TiO2-PW catalyst and molecular sieve adsorption and decolorization, combined with ethanol recrystallization treatment, optimize the DCP preparation process; in thermal curing ink, graphene nanosheets, hyperbranched polyester acrylate and other materials are modified.
Significantly improve DCP yield and purity, reduce by-product content, improve ink conductivity and wear resistance, shorten curing time, enhance adhesion, and improve the comprehensive performance of ink.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dicumyl peroxide production, in particular to dicumyl peroxide and a preparation method and application thereof. Background Art
[0002] As an important organic peroxide, dicumyl peroxide (DCP) plays an irreplaceable role in many industrial fields. In the rubber vulcanization process, it can promote the cross-linking reaction of rubber molecular chains, improve the strength, elasticity and wear resistance of rubber, and is widely used in the production of rubber products such as tires and seals; in terms of plastic cross-linking, DCP can transform the molecular structure of plastics from linear to three-dimensional network, thereby improving the heat resistance, chemical stability and mechanical properties of plastics, and is widely used in the production of plastic products such as pipes and plates.
[0003] However, the current preparation technology of DCP has many disadvantages. From the perspective of catalysts, concentrated sulfuric acid is often used as a catalyst in traditional processes. Although concentrated sulfuric acid can promote the reaction to a certain extent, it is highly corrosive and causes great loss to production equipment. The annual corrosion rate of equipment exceeds 0.1mm, which not only increases the cost of equipment maintenance and replacement, but also poses safety hazards; at the same time, the reaction will produce a large amount of waste acid that is difficult to handle, which is costly to handle and does not meet the current strict environmental protection requirements. In terms of catalytic effect, the existing catalytic system has poor activity and selectivity, resulting in frequent side reactions during the reaction, such as the sulfonation reaction of isopropylbenzene, which makes the product purity generally low, usually less than 98%, and the yield is not ideal, generally less than 85%. Moreover, the content of by-products (such as isopropylphenol) in the product is high, exceeding 5%, which undoubtedly increases the difficulty and cost of subsequent product purification. In addition, there are also problems with the stability and safety of the reaction system. Hydrogen peroxide (H2O2) has poor stability and is easy to decompose during the reaction, with a decomposition rate of more than 15%, which not only reduces the utilization rate of raw materials, but also may cause the reaction to run away; metal ions (such as Fe 3+ , Cu 2+ ) will catalyze the homolytic splitting of H2O2 to generate hydroxyl radicals (·OH), further aggravating the occurrence of side reactions and affecting product quality and production safety.
[0004] The demand for thermosetting inks in the electronic circuit, packaging and printing industries continues to grow. In the field of electronic circuits, when used in electronic components such as printed circuit boards, the ink's conductivity, adhesion and wear resistance are extremely high; in the packaging and printing industry, the ink needs to have good color expression, weather resistance and compatibility with different packaging materials. However, existing thermosetting inks have obvious technical bottlenecks. In terms of performance, traditional thermosetting inks have relatively single functions. Its conductivity is extremely poor, and its surface resistance is as high as 10 15Ω / sq, far from meeting the application scenarios with strict requirements on conductivity such as electronic packaging; when the resin content is increased to improve the wear resistance of the ink, the curing shrinkage rate will increase significantly, exceeding 3%, which reduces the adhesion of the coating on the printed substrate. The adhesion level is ≥1 through the cross-cutting method test, affecting the printing quality and the service life of the product. In terms of dispersion and stability, the pigments, fillers and other components in traditional inks are unevenly dispersed, and are prone to agglomeration and sedimentation during storage and use, resulting in uneven color and reduced pattern clarity during printing; and the single thermal curing method in the existing process requires long-term (>5 minutes) treatment at high temperature (140-150°C), which is not only energy-intensive, but also not suitable for heat-sensitive substrates, limiting the application scope of thermal curing inks. Summary of the invention
[0005] In view of the above deficiencies in the prior art, the object of the present invention is to provide a dicumyl peroxide, which effectively inhibits the decomposition of hydrogen peroxide by adopting a composite stabilizer, reduces the decomposition rate from 15% to 2.5%, significantly improves the stability of the reaction system, reduces the occurrence of side reactions, and greatly reduces the content of by-products.
[0006] Another object of the present invention is to provide a method for preparing dicumyl peroxide, which improves the yield of DCP, reduces the content of by-products, and makes the product purer by controlling the reaction temperature and time, as well as molecular sieve adsorption decolorization and ethanol recrystallization treatment.
[0007] The third object of the present invention is to provide an application of dicumyl peroxide, and the prepared heat curing ink has good comprehensive properties. The surface resistance is as low as 1.2×10 6 Ω / sq, with excellent conductivity, which can meet the printing needs of electronic circuits and other printings that require ink conductivity.
[0008] The present invention is achieved by adopting the following technical solutions: The preparation method of dicumyl peroxide comprises the following steps: (1) Mix cumene and composite stabilizer and dehydrate under reduced pressure at 60°C until the water content is ≤30ppm; (2) adding hydrogen peroxide and TiO2-PW catalyst, reacting at 65°C for 1.5 hours under nitrogen protection; then raising the temperature to 85°C for 4 hours, during which TiO2-PW catalyst was added to obtain a reaction solution; (3) The reaction solution obtained in step (2) is cooled to 40° C., and the catalyst is recovered by filtration; the aqueous phase is separated and the organic phase is washed with a 4-6% sodium bicarbonate solution until it is neutral; unreacted cumene is removed by vacuum distillation, and then decolorized by molecular sieve adsorption and recrystallized with ethanol, and dried to obtain dicumyl peroxide; The composite stabilizer is obtained by mixing disodium ethylenediaminetetraacetate (EDTA-2Na) and sodium pyrophosphate (TSPP) in a mass ratio of 1:1; The TiO2-PW catalyst is a composite catalyst composed of titanium dioxide and phosphotungstic acid.
[0009] Molecular sieve adsorption decolorization includes the following steps: Molecular sieve pretreatment: 3A molecular sieve (pore size 0.3nm, used to adsorb small molecule pigments and moisture).
[0010] Activation conditions: temperature: 300°C; time: 4 hours; atmosphere: nitrogen protection.
[0011] Adsorption decolorization: Molecular sieve dosage: 5% of the crude product mass; temperature: 40±2°C; time: 2 hours (mechanical stirring, rotation speed 100rpm); endpoint control: solution transmittance ≥95% (UV-Vis detection, wavelength 450nm).
[0012] Filtration separation: Filtration equipment: plate and frame filter press (filter cloth pore size 1 μm); Washing: rinse the filter cake with 10% ethanol solution (volume ratio 1:1).
[0013] 3A molecular sieve selectively adsorbs small molecular pigments (such as cumene oxidation products) and removes trace amounts of water (to avoid abnormal growth of crystal nuclei during recrystallization). Compared with traditional activated carbon, molecular sieve does not adsorb DCP, and the product loss rate is less than 0.5%.
[0014] Ethanol recrystallization comprises the following steps: The crude product was dissolved in solvent in a ratio of crude DCP to ethanol = 1:4 (mass ratio); temperature: 60°C (reflux dissolution, time 30 minutes).
[0015] Gradient cooling crystallization: cooling program: 60℃→40℃ (rate 1℃ / min); 40℃→25℃ (rate 0.5℃ / min); standing at 25℃: 4 hours.
[0016] Filtration and drying: filtration through a Buchner funnel (vacuum degree -0.08MPa); washing with cold ethanol (0-5℃) twice (each time the amount is 1 times the volume of the crystal); drying: temperature: 35℃ (vacuum drying oven); time: 12 hours; finished product indicators: purity ≥99.8% (HPLC), melting point 39.0-39.3℃ (DSC determination).
[0017] Gradient cooling is used to control the crystal growth rate and avoid impurities being encapsulated, and cold ethanol washing is used to remove residual low-melting-point byproducts (such as diisopropylphenyl ether) on the surface.
[0018] The molar ratio of cumene to hydrogen peroxide is 1:(1.05-1.15), the amount of TiO2-PW catalyst added is 0.3-1.0% of the mass of cumene, and the amount of composite stabilizer added is 0.2-0.4% of the mass of cumene; in step (2), the added TiO2-PW catalyst accounts for 0.1% of the total mass of the TiO2-PW catalyst added.
[0019] The purity of the dicumyl peroxide is ≥99.8%, and the melting point is 38.5-39.5°C.
[0020] The preparation method of the TiO2-PW catalyst comprises the following steps: a. Calcine nano-TiO2 at 300°C for 2 hours; b. The nano-TiO2 treated in step a was immersed in a 0.5 mol / L phosphotungstic acid aqueous solution and ultrasonically dispersed for 1 hour to obtain a mixed solution; c. The mixed solution obtained in step b was evaporated to dryness at 80 ℃, dried at 120 ℃, and calcined at 500 ℃ for 3 hours to obtain a TiO2-PW catalyst.
[0021] The particle size of the nano-TiO2 is 20nm, the specific surface area is ≥150m² / g, and the loading amount of the TiO2-PW catalyst is 10-15wt%.
[0022] In the preparation process of DCP, composite stabilizers play a key role. Disodium EDTA can chelate metal ions (such as Fe 3+ ), so that the residual Fe 3+ ≤0.1ppm, effectively inhibiting the decomposition reaction of H2O2 under the catalysis of metal ions; sodium pyrophosphate avoids the sulfonation side reaction of isopropylbenzene under acidic conditions by adjusting the pH value of the reaction solution to 5.5-6.0, thereby reducing the formation of by-products. The mechanism of action of the TiO2-PW catalyst is that nano-TiO2 provides a large specific surface area, allowing phosphotungstic acid to be highly dispersed and stably loaded, and the Ti-OW bonding structure gives the catalyst a unique catalytic active site. At 65°C, the reaction starts smoothly, which is conducive to the activation of hydrogen peroxide; when the temperature is raised to 85°C, the reaction rate accelerates, promoting the condensation reaction, and staged temperature control allows the reaction to proceed efficiently and orderly. In the purification stage after the reaction, the 3A molecular sieve can selectively adsorb small molecular pigments and water due to its specific pore size (0.3nm), while avoiding the adsorption of DCP and reducing product loss; in the ethanol gradient recrystallization process, by controlling the cooling rate (60℃→40℃ rate is 1℃ / min, 40℃→25℃ rate is 0.5℃ / min), the DCP crystals grow slowly and evenly, effectively avoiding the inclusion of impurities, thereby improving the purity of the product.
[0023] The dicumyl peroxide is prepared by the above preparation method of dicumyl peroxide.
[0024] The dicumyl peroxide is used for preparing heat curing ink.
[0025] The method for preparing the thermosetting ink comprises the following steps: Ⅰ. Epoxy acrylic resin, hyperbranched polyester acrylate, trimethylolpropane triacrylate, dicumyl peroxide, graphene nanosheets, pigments and additives were mixed at 60° C. with a planetary mixer for 30 minutes to form a homogeneous system to obtain a premix; Ⅱ. Graphene and trimethylolpropane triacrylate were premixed in a mass ratio of 1:10, and ball-milled at 400 rpm for 2 hours to form a graphene dispersion; the graphene dispersion was added to the premix, and high-speed sheared at 2000 rpm for 1 hour to a fineness of ≤20 μm; III. Then grind it three times with a tungsten carbide three-roll mill to make the fineness ≤5μm; then filter it through a 500-mesh filter under nitrogen pressure, and control the viscosity of the finished product to 2800-3200cps to obtain a thermosetting ink.
[0026] The pigment is phthalocyanine blue BGS, and the additives include leveling agent BYK-333, defoaming agent TegoFoamex810, nano-silica and benzophenone; the roller gap pressure of the tungsten carbide three-roller machine is 0.2-0.3MPa; the trimethylolpropane triacrylate used in step I is 70-80% of its total amount; the trimethylolpropane triacrylate used in step II is 20-30% of its total amount.
[0027] The mass percentage of each raw material is: epoxy acrylic resin (EA): 35-45%; hyperbranched polyester acrylate (HBPEA): 10-15%; trimethylolpropane triacrylate (TMPTA): 12-18%; diisopropylbenzene peroxide: 3-5%; graphene nanosheets: 0.1-0.5%; phthalocyanine blue BGS: 10-12%; nano-silica: 8-12%; benzophenone: 1-2%; leveling agent BYK-333: 0.5-1%; defoaming agent TegoFoamex810: 0.3-0.8%; graphene: 1.2-1.8%.
[0028] In the preparation process of thermosetting ink, the raw materials cooperate with each other to achieve a synergistic improvement in performance. Graphene nanosheets have excellent conductivity and mechanical properties. After ball milling and dispersion, their ultra-thin sheets are evenly distributed in the ink system and interfacially bonded with the free radicals generated by the decomposition of DCP, which not only builds a conductive path but also enhances the wear resistance of the ink. The three-dimensional structure of hyperbranched polyester acrylate (HBPEA) enables it to reduce viscosity in the system, which is conducive to the uniform dispersion of various components; its multiple acrylate groups can cross-link with the free radicals generated by the decomposition of DCP to form a dense three-dimensional cross-linked network, thereby reducing the curing shrinkage and improving the adhesion and hardness of the ink. Benzophenone (BP) as a photoinitiator can quickly generate free radicals under UV irradiation, triggering a pre-curing reaction, so that the ink is initially cured in a short time; DCP further decomposes and generates free radicals during the subsequent heating process at 130°C, prompting the resin and acrylate monomers to fully cross-link and achieve deep curing, making up for the shortcomings of UV curing and improving the overall curing effect and performance of the ink. Epoxy acrylic resin and hyperbranched polyester acrylate are the main film-forming substances, providing the basic properties of the ink. Trimethylolpropane triacrylate participates in the cross-linking reaction to enhance the hardness and wear resistance of the ink. Diisopropylbenzene peroxide decomposes under heating conditions to produce free radicals, which trigger the cross-linking reaction between the resin and acrylate monomers to form a three-dimensional network structure, so that the ink is cured into a film. The pigment phthalocyanine blue BGS gives the ink color, nano-silica can adjust the rheological properties of the ink and promote the cross-linking reaction during the heating process, and the leveling agent BYK-333 and the defoaming agent TegoFoamex810 respectively improve the leveling of the ink and eliminate bubbles. The raw materials cooperate with each other to jointly improve the comprehensive performance of the thermosetting ink.
[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) By using a composite stabilizer (a mixture of disodium ethylenediaminetetraacetic acid and sodium pyrophosphate in a mass ratio of 1:1), the decomposition of hydrogen peroxide was effectively inhibited, and the decomposition rate was reduced from 15% to 2.5%. The stability of the reaction system was significantly improved, the occurrence of side reactions was reduced, and the content of by-products was greatly reduced. The TiO2-PW catalyst used has a unique Lewis acid site (TiO2-PW) by virtue of the Ti-OW bonding structure formed by the nano-TiO2 carrier (specific surface area ≥ 150m² / g) loaded with phosphotungstic acid (PW). 4+) and redox active sites (W=O bonds), greatly improving the catalytic efficiency. The reaction conditions of staged temperature control (65℃→85℃) accurately match the H2O2 activation and condensation reaction kinetics, so that the DCP yield reaches 95.1%, which is much higher than the 82.3% of traditional sulfuric acid catalysis. In addition, the catalyst can be recycled more than 10 times, and the activity can still be maintained above 95% after recycling. In the purification process, molecular sieve adsorption decolorization (3A molecular sieve) is used to selectively remove small molecule pigments, avoiding product loss caused by traditional activated carbon adsorption, and the product loss rate is less than 0.5%; the ethanol gradient recrystallization (60℃→25℃) process can accurately control crystal growth, and the purity of the final DCP is increased to more than 99.8% (HPLC detection), which effectively improves the product quality.
[0030] (2) Graphene nanosheets (0.1-0.5%) were dispersed by ball milling to form ultra-thin sheets (≤5nm), which were interfacially bonded (COC) with DCP free radicals to successfully construct a conductive path, making the surface resistance of the ink as low as 10 6 Ω / sq, and significantly improved the wear resistance. According to the Taber test, the weight loss was only 8mg / 1000 times. Hyperbranched polyester acrylate (HBPEA) reduces the viscosity of the system with its three-dimensional structure. Its high functionality (6-8 acrylate groups) synergizes with DCP to form a dense cross-linked network, reducing the curing shrinkage to 1.2%, which is significantly lower than that of traditional inks, effectively improving the comprehensive performance of the ink. The application of light and heat dual-curing system is also very advantageous. Benzophenone (BP) triggers pre-curing under UV irradiation (500mJ / cm²), which greatly reduces the heat curing time from 8 minutes of traditional single heat curing to 3 minutes; DCP is deeply cross-linked at 130°C, which makes up for the problem of insufficient penetration of UV curing, so that the hardness of the ink reaches 2H (ASTMD3363) and the adhesion reaches level 0 (no shedding), which greatly improves the curing effect of the ink and the coating quality. DETAILED DESCRIPTION
[0031] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail below.
[0032] Sources of some raw materials in the following examples, comparative examples, application examples and application comparative examples: Ethylenediaminetetraacetic acid disodium (EDTA-2Na): Nantong Aokai Biotechnology Development Co., Ltd.; Sodium pyrophosphate (TSPP): Shanghai Yiji Industrial Co., Ltd.; Nano titanium dioxide (TiO2): Shanghai Huijingya Nano New Materials Co., Ltd.; Epoxy acrylic resin: Changxing Chemical Industry Co., Ltd. Hyperbranched polyester acrylate: DSM Group; Trimethylolpropane triacrylate: BASF; Graphene nanosheets: Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; Phthalocyanine Blue BGS: BASF; Nanosilica: Cabot Corporation; Benzophenone: Shandong Jinling Chemical Co., Ltd.; Leveling agent BYK-333: BYK; Defoamer TegoFoamex810: Evonik Industries AG.
[0033] Test method: DCP yield: According to the chemical reaction equation, the theoretical mass of dicumyl peroxide that should be generated is calculated based on the amount of cumene added in the reaction. After the reaction is completed, the dicumyl peroxide product is separated and dried, and its mass is accurately weighed. Yield = (actual product mass ÷ theoretical product mass) × 100%.
[0034] DCP purity (HPLC): GB / T22313-2008 "Determination of the purity of toluene diisocyanate used in the production of polyurethane plastics".
[0035] DCP by-product content (GC): GB / T30921.2-2016 "Test method for industrial purified terephthalic acid (PTA) Part 2: Determination of p-carboxybenzaldehyde (4-CBA) and p-toluic acid (p-TOL) content".
[0036] Catalyst cycle times and activity: After each reaction, filter and recover the catalyst, wash with an appropriate solvent (such as ethanol) and dry. Use the recovered catalyst for the dicumyl peroxide preparation reaction under the same conditions, and repeat multiple times (10 times). Determine the yield of the product after each reaction, and calculate the retention rate of the subsequent reaction yield based on the yield of the first reaction to evaluate the catalyst's cyclic activity.
[0037] Ink surface resistance: GB / T2439-2001 "Determination of electrical conductivity and dissipative resistivity of vulcanized rubber or thermoplastic rubber").
[0038] Ink adhesion (cross-cut method): GB / T9286-1998 "Cross-cut test for paint and varnish films".
[0039] Ink abrasion resistance: Tested using Taber abrasion tester in accordance with relevant industry standards (ASTM D4060 "Standard Test Method for Abrasion Resistance of Organic Coatings Using Taber Abrasion Tester").
[0040] Ink curing shrinkage: GB / T1682-2014 "Single specimen method for determination of low temperature brittleness of vulcanized rubber".
[0041] Ink curing time: Place the test plate coated with ink in an oven at 130°C. Take out the test plate at regular intervals (1 minute), use a hardness test pen or other suitable tools to check the curing degree of the ink, and record the time (minutes) required for the ink to fully cure.
[0042] Ink resistance to ethanol wiping: Dip a cotton ball in anhydrous ethanol, apply a certain pressure (500g / cm²) on the surface of the cured ink film, and wipe back and forth at a constant speed (30 times / minute). Record the number of wipes when the ink film shows obvious discoloration (lighter color, scratches appear).
[0043] In the following examples and comparative examples, the specific processing conditions for molecular sieve adsorption decolorization and ethanol recrystallization are: Molecular sieve adsorption decolorization includes the following steps: Molecular sieve pretreatment: 3A molecular sieve (pore size 0.3nm, used to adsorb small molecule pigments and moisture).
[0044] Activation conditions: temperature: 300°C; time: 4 hours; atmosphere: nitrogen protection.
[0045] Adsorption decolorization: Molecular sieve dosage: 5% of the crude product mass; temperature: 40°C; time: 2 hours (mechanical stirring, rotation speed 100 rpm); endpoint control: solution transmittance is 95% (UV-Vis detection, wavelength 450 nm).
[0046] Filtration separation: Filtration equipment: plate and frame filter press (filter cloth pore size 1 μm); Washing: rinse the filter cake with 10% ethanol solution (volume ratio 1:1).
[0047] 3A molecular sieve selectively adsorbs small molecular pigments and removes trace amounts of water. Compared with traditional activated carbon, the molecular sieve does not adsorb DCP and the product loss rate is 0.3%.
[0048] Ethanol recrystallization comprises the following steps: The crude product was dissolved in solvent in a ratio of crude DCP to ethanol = 1:4 (mass ratio); temperature: 60°C (reflux dissolution, time 30 minutes).
[0049] Gradient cooling crystallization: cooling program: 60℃→40℃ (rate 1℃ / min); 40℃→25℃ (rate 0.5℃ / min); standing at 25℃: 4 hours.
[0050] Filtration and drying: filtration through a Buchner funnel (vacuum degree -0.08MPa); washing twice with cold ethanol (0-5°C) (each time the amount is 1 times the volume of the crystals); drying: temperature: 35°C (vacuum drying oven); time: 12 hours.
[0051] Example 1 The preparation method of TiO2-PW catalyst comprises the following steps: a. Calcine nano-TiO2 at 300°C for 2 hours; b. The nano-TiO2 treated in step a was immersed in a 0.5 mol / L phosphotungstic acid aqueous solution and ultrasonically dispersed for 1 hour to obtain a mixed solution; c. The mixed solution obtained in step b was evaporated to dryness at 80 ℃, dried at 120 ℃, and calcined at 500 ℃ for 3 hours to obtain a TiO2-PW catalyst.
[0052] The particle size of nano-TiO2 is 20nm, the specific surface area is 150m² / g, and the loading amount of TiO2-PW catalyst is 12wt%.
[0053] The preparation method of dicumyl peroxide comprises the following steps: (1) Mix cumene and composite stabilizer and dehydrate under reduced pressure at 60°C until the water content is 30 ppm; (2) adding hydrogen peroxide and TiO2-PW catalyst, reacting at 65°C for 1.5 hours under nitrogen protection; then raising the temperature to 85°C for 4 hours, during which TiO2-PW catalyst was added to obtain a reaction solution; (3) The reaction solution obtained in step (2) is cooled to 40° C., and the catalyst is recovered by filtration; the aqueous phase is separated and the organic phase is washed with a 5% sodium bicarbonate solution until it is neutral; unreacted cumene is removed by vacuum distillation, and then decolorized by molecular sieve adsorption and recrystallized with ethanol, and dried to obtain dicumyl peroxide; The composite stabilizer is obtained by mixing disodium ethylenediaminetetraacetate and sodium pyrophosphate in a mass ratio of 1:1.
[0054] The molar ratio of cumene to hydrogen peroxide is 1:1.1, the amount of TiO2-PW catalyst added is 0.6% of the mass of cumene, and the amount of composite stabilizer added is 0.3% of the mass of cumene; in step (2), the added TiO2-PW catalyst accounts for 0.1% of the total mass of the TiO2-PW catalyst added.
[0055] Example 2 The preparation method of TiO2-PW catalyst comprises the following steps: a. Calcine nano-TiO2 at 300°C for 2 hours; b. The nano-TiO2 treated in step a was immersed in a 0.5 mol / L phosphotungstic acid aqueous solution and ultrasonically dispersed for 1 hour to obtain a mixed solution; c. The mixed solution obtained in step b was evaporated to dryness at 80 ℃, dried at 120 ℃, and calcined at 500 ℃ for 3 hours to obtain a TiO2-PW catalyst.
[0056] The particle size of nano-TiO2 is 20nm, the specific surface area is 150m² / g, and the loading amount of TiO2-PW catalyst is 15wt%.
[0057] The preparation method of dicumyl peroxide comprises the following steps: (1) Mix cumene and composite stabilizer and dehydrate under reduced pressure at 60°C until the water content is 30 ppm; (2) adding hydrogen peroxide and TiO2-PW catalyst, reacting at 65°C for 1.5 hours under nitrogen protection; then raising the temperature to 85°C for 4 hours, during which TiO2-PW catalyst was added to obtain a reaction solution; (3) The reaction solution obtained in step (2) is cooled to 40° C., and the catalyst is recovered by filtration; the aqueous phase is separated and the organic phase is washed with a 4% sodium bicarbonate solution until it is neutral; unreacted cumene is removed by vacuum distillation, and then decolorized by molecular sieve adsorption and recrystallized with ethanol, and dried to obtain dicumyl peroxide; The composite stabilizer is obtained by mixing disodium ethylenediaminetetraacetate and sodium pyrophosphate in a mass ratio of 1:1.
[0058] The molar ratio of cumene to hydrogen peroxide is 1:1.15, the amount of TiO2-PW catalyst added is 1.0% of the mass of cumene, and the amount of composite stabilizer added is 0.4% of the mass of cumene; in step (2), the added TiO2-PW catalyst accounts for 0.1% of the total mass of the TiO2-PW catalyst added.
[0059] Example 3 The preparation method of TiO2-PW catalyst comprises the following steps: a. Calcine nano-TiO2 at 300°C for 2 hours; b. The nano-TiO2 treated in step a was immersed in a 0.5 mol / L phosphotungstic acid aqueous solution and ultrasonically dispersed for 1 hour to obtain a mixed solution; c. The mixed solution obtained in step b was evaporated to dryness at 80 ℃, dried at 120 ℃, and calcined at 500 ℃ for 3 hours to obtain a TiO2-PW catalyst.
[0060] The particle size of nano-TiO2 is 20nm, the specific surface area is 150m² / g, and the loading amount of TiO2-PW catalyst is 10wt%.
[0061] The preparation method of dicumyl peroxide comprises the following steps: (1) Mix cumene and composite stabilizer and dehydrate under reduced pressure at 60°C until the water content is 30 ppm; (2) adding hydrogen peroxide and TiO2-PW catalyst, reacting at 65°C for 1.5 hours under nitrogen protection; then raising the temperature to 85°C for 4 hours, during which TiO2-PW catalyst was added to obtain a reaction solution; (3) The reaction solution obtained in step (2) is cooled to 40° C., and the catalyst is recovered by filtration; the aqueous phase is separated and the organic phase is washed with a 6% sodium bicarbonate solution until it is neutral; unreacted cumene is removed by vacuum distillation, and then decolorized by molecular sieve adsorption and recrystallized with ethanol, and dried to obtain dicumyl peroxide; The composite stabilizer is obtained by mixing disodium ethylenediaminetetraacetate and sodium pyrophosphate in a mass ratio of 1:1.
[0062] The molar ratio of cumene to hydrogen peroxide is 1:1.05, the amount of TiO2-PW catalyst added is 0.3% of the mass of cumene, and the amount of composite stabilizer added is 0.2% of the mass of cumene; in step (2), the added TiO2-PW catalyst accounts for 0.1% of the total mass of the TiO2-PW catalyst added.
[0063] Comparative Example 1 The difference from Example 1 is that EDTA-2Na is used as the stabilizer.
[0064] Comparative Example 2 The difference from Example 2 is that the catalyst is changed to concentrated sulfuric acid.
[0065] Comparative Example 3 The difference from Example 3 is that the molecular sieve used is HZSM-5 molecular sieve.
[0066] Comparative Example 4 The difference from Example 1 is that no stabilizer is added.
[0067] Comparative Example 5 The difference from Example 1 is that the reaction temperature is 85° C. and the reaction time is 6 hours.
[0068] Comparative Example 6 The difference from Example 1 is that molecular sieve is not used for decolorization. The prepared diisopropylbenzene peroxide is yellow in color (small molecular pigment is not selectively adsorbed), and the trace amount of residual moisture is greater than 30 ppm, which affects the recrystallization process (abnormal growth of crystal nuclei) and reduces the uniformity of the crystal.
[0069] The test data of Examples 1-3 and Comparative Examples 1-6 are shown in Table 1.
[0070] Table 1: Test data of Examples 1-3 and Comparative Examples 1-6
[0071] Through the analysis of Table 1, it can be seen that: by chelating metal ions (Fe 3+ ≤0.1ppm), reduce side reactions (by-product content ≤1.5%); nano-TiO2 (specific surface area ≥150m² / g) loaded with phosphotungstic acid to form a Ti-OW bonding structure, with Lewis acid sites (Ti 4+ ) and redox active sites (W=O), with high catalytic efficiency (yield up to 95.1%), and can be recycled for more than 10 times (activity retention ≥90%). The reaction efficiency is improved by matching the H2O2 activation and condensation kinetics through temperature control (65℃→85℃).
[0072] Application Example 1 The preparation method of heat curing ink comprises the following steps: Ⅰ. The epoxy acrylic resin, hyperbranched polyester acrylate, trimethylolpropane triacrylate, dicumyl peroxide obtained in Example 1, graphene nanosheets, pigments and additives were mixed at 60 ° C for 30 minutes with a planetary mixer to form a homogeneous system to obtain a premix; Ⅱ. Graphene and trimethylolpropane triacrylate were premixed in a mass ratio of 1:10, and ball-milled at 400 rpm for 2 hours to form a graphene dispersion; the graphene dispersion was added to the premix, and high-speed sheared at 2000 rpm for 1 hour to a fineness of 20 μm; III. Then, the mixture was ground three times using a tungsten carbide three-roll mill to a fineness of 5 μm; the mixture was then filtered through a 500-mesh filter under nitrogen pressure, and the viscosity of the finished product was controlled to be 3000 cps to obtain a thermosetting ink.
[0073] The pigment is phthalocyanine blue BGS, and the additives include leveling agent BYK-333, defoaming agent TegoFoamex810, nano-silica and benzophenone; the roller gap pressure of the tungsten carbide three-roller machine is 0.3MPa; the trimethylolpropane triacrylate used in step I is 75% of its total amount; the trimethylolpropane triacrylate used in step II is 25% of its total amount.
[0074] The mass percentage of each raw material is: epoxy acrylic resin: 42%; hyperbranched polyester acrylate: 13%; trimethylolpropane triacrylate: 15%; diisopropylbenzene peroxide: 4%; graphene nanosheets: 0.3%; phthalocyanine blue BGS: 11%; nano-silica: 10%; benzophenone: 1.5%; leveling agent BYK-333: 1%; defoaming agent TegoFoamex810: 0.7%; and graphene: 1.5%.
[0075] Application Example 2 The preparation method of heat curing ink comprises the following steps: Ⅰ. The epoxy acrylic resin, hyperbranched polyester acrylate, trimethylolpropane triacrylate, dicumyl peroxide obtained in Example 1, graphene nanosheets, pigments and additives were mixed at 60 ° C for 30 minutes with a planetary mixer to form a homogeneous system to obtain a premix; Ⅱ. Graphene and trimethylolpropane triacrylate were premixed in a mass ratio of 1:10, and ball-milled at 400 rpm for 2 hours to form a graphene dispersion; the graphene dispersion was added to the premix, and high-speed sheared at 2000 rpm for 1 hour to a fineness of 20 μm; III. Then, the mixture was ground three times using a tungsten carbide three-roll mill to a fineness of 5 μm. The mixture was then filtered through a 500-mesh filter under nitrogen pressure, and the viscosity of the finished product was controlled to be 2800 cps to obtain a thermosetting ink.
[0076] The pigment is phthalocyanine blue BGS, the additives include leveling agent BYK-333, defoaming agent TegoFoamex810, nano-silica and benzophenone; the roller gap pressure of the tungsten carbide three-roller machine is 0.2MPa; the trimethylolpropane triacrylate used in step I is 70% of its total amount; the trimethylolpropane triacrylate used in step II is 30% of its total amount.
[0077] The mass percentage of each raw material is: epoxy acrylic resin: 45%; hyperbranched polyester acrylate: 10%; trimethylolpropane triacrylate: 14%; diisopropylbenzene peroxide: 5%; graphene nanosheets: 0.5%; phthalocyanine blue BGS: 12%; nano-silica: 8.6%; benzophenone: 2%; leveling agent BYK-333: 0.7%; defoaming agent TegoFoamex810: 0.8%; graphene: 1.4%.
[0078] Application Example 3 The preparation method of heat curing ink comprises the following steps: Ⅰ. The epoxy acrylic resin, hyperbranched polyester acrylate, trimethylolpropane triacrylate, dicumyl peroxide obtained in Example 2, graphene nanosheets, pigments and additives were mixed at 60 ° C for 30 minutes with a planetary mixer to form a homogeneous system to obtain a premix; Ⅱ. Graphene and trimethylolpropane triacrylate were premixed in a mass ratio of 1:10, and ball-milled at 400 rpm for 2 hours to form a graphene dispersion; the graphene dispersion was added to the premix, and high-speed sheared at 2000 rpm for 1 hour to a fineness of 20 μm; III. Then, the mixture was ground three times using a tungsten carbide three-roll mill to a fineness of 5 μm. The mixture was then filtered through a 500-mesh filter under nitrogen pressure, and the viscosity of the finished product was controlled to be 3200 cps to obtain a thermosetting ink.
[0079] The pigment is phthalocyanine blue BGS, the additives include leveling agent BYK-333, defoaming agent TegoFoamex810, nano-silica and benzophenone; the roller gap pressure of the tungsten carbide three-roller machine is 0.2-0.3MPa; the trimethylolpropane triacrylate used in step I is 80% of its total amount; the trimethylolpropane triacrylate used in step II is 20% of its total amount.
[0080] The mass percentage of each raw material is: epoxy acrylic resin: 35%; hyperbranched polyester acrylate: 13.2%; trimethylolpropane triacrylate: 18%; diisopropylbenzene peroxide: 5%; graphene nanosheets: 0.2%; phthalocyanine blue BGS: 11%; nano-silica: 12%; benzophenone: 2%; leveling agent BYK-333: 1%; defoaming agent TegoFoamex810: 0.8%; graphene: 1.8%.
[0081] Application Comparative Example 1 The difference from Application Example 1 is that graphene is not added; Application Comparative Example 2 The difference from Application Example 2 is that HBPEA is not added.
[0082] Application Comparative Example 3 The difference from Application Example 3 is that DCP is replaced by dibenzoyl peroxide (BPO).
[0083] Application Comparative Example 4 The difference from Application Example 1 is that BP was not added (thermal curing only).
[0084] Application Comparative Example 5 The difference from Application Example 1 is that the DCP prepared in Comparative Example 1 is used.
[0085] In the performance test of the heat curing ink, it is necessary to perform a standardized coating operation on the ink obtained from the application example and the application comparative example, and the specific steps are as follows: Substrate pretreatment: Select a printed circuit board (PCB) as the substrate, wipe the surface with anhydrous ethanol to remove grease and dust, and set it aside after drying.
[0086] Ink coating: Pour the ink into the coater and use a wire rod coater (wire diameter 25μm) to coat the surface of the substrate, controlling the wet film thickness to 20μm. After coating, let it stand for 5 minutes (room temperature 25℃) to allow the ink to level out.
[0087] Curing treatment: UV pre-curing: Use a UV curing machine (wavelength 365nm, light intensity 500mJ / cm²) for 3 minutes to make the ink initially cross-linked.
[0088] Thermal curing: Place the pre-cured sample in a 130°C oven and heat for 3 minutes to complete deep curing.
[0089] Test sample preparation: The cured ink film needs to be placed in a constant temperature and humidity environment (25°C, 50% humidity) for 24 hours to ensure that the performance is stable before subsequent testing.
[0090] The test data of application examples 1-3 and application comparative examples 1-5 are shown in Table 2.
[0091] Table 2: Test data of application examples 1-3 and application comparative examples 1-5
[0092] From the analysis of Table 2, it can be seen that: in terms of conductivity, graphene nanosheets (0.1-0.5%) construct conductive paths with a surface resistance as low as 1.2×10 6 Ω / sq. In terms of wear resistance and adhesion, hyperbranched polyester acrylate (HBPEA) and DCP synergistically crosslinked, the curing shrinkage rate was reduced to 1.2% (conventional 3.5%), and the adhesion reached level 0 (no shedding). UV pre-curing (3 minutes) combined with DCP thermal curing (130°C) shortened the total curing time to 3 minutes, and the hardness reached 2H.
Claims
1. A method for preparing dicumyl peroxide, characterized in that: The following steps are involved: (1) Mix cumene and composite stabilizer and dehydrate under reduced pressure at 60°C until the water content is ≤30ppm; (2) adding hydrogen peroxide and TiO2-PW catalyst, reacting at 65°C for 1.5 hours under nitrogen protection; then raising the temperature to 85°C for 4 hours, during which TiO2-PW catalyst was added to obtain a reaction solution; (3) The reaction solution obtained in step (2) is cooled to 40° C., and the catalyst is recovered by filtration; the aqueous phase is separated and the organic phase is washed with a 4-6% sodium bicarbonate solution until it is neutral; unreacted cumene is removed by vacuum distillation, and then decolorized by molecular sieve adsorption and recrystallized with ethanol, and dried to obtain dicumyl peroxide; The composite stabilizer is obtained by mixing disodium ethylenediaminetetraacetate and sodium pyrophosphate in a mass ratio of 1:1; The TiO2-PW catalyst is a composite catalyst composed of titanium dioxide and phosphotungstic acid.
2. The method for preparing dicumyl peroxide according to claim 1, characterized in that: The molar ratio of cumene to hydrogen peroxide is 1:(1.05-1.15), the amount of TiO2-PW catalyst added is 0.3-1.0% of the mass of cumene, and the amount of composite stabilizer added is 0.2-0.4% of the mass of cumene; in step (2), the added TiO2-PW catalyst accounts for 0.1% of the total mass of the TiO2-PW catalyst added.
3. The method for preparing dicumyl peroxide according to claim 1, characterized in that: The purity of the dicumyl peroxide is ≥99.8%, and the melting point is 38.5-39.5°C.
4. The method for preparing dicumyl peroxide according to claim 1, characterized in that: The preparation method of the TiO2-PW catalyst comprises the following steps: a. Calcine nano-TiO2 at 300°C for 2 hours; b. The nano-TiO2 treated in step a was immersed in a 0.5 mol / L phosphotungstic acid aqueous solution and ultrasonically dispersed for 1 hour to obtain a mixed solution; c. The mixed solution obtained in step b was evaporated to dryness at 80 ℃, dried at 120 ℃, and calcined at 500 ℃ for 3 hours to obtain a TiO2-PW catalyst.
5. The method for preparing dicumyl peroxide according to claim 4, characterized in that: The particle size of the nano-TiO2 is 20nm, the specific surface area is ≥150m² / g, and the loading amount of the TiO2-PW catalyst is 10-15wt%.
6. A dicumyl peroxide, characterized in that: The dicumyl peroxide is prepared by the preparation method of any one of claims 1 to 5.
7. An application of dicumyl peroxide according to claim 6, characterized in that: Used to prepare heat-curing inks.
8. The use of dicumyl peroxide according to claim 7, characterized in that: The method for preparing the thermosetting ink comprises the following steps: Ⅰ. Epoxy acrylic resin, hyperbranched polyester acrylate, trimethylolpropane triacrylate, dicumyl peroxide, graphene nanosheets, pigments and additives were mixed at 60° C. with a planetary mixer for 30 minutes to form a homogeneous system to obtain a premix; Ⅱ. Graphene and trimethylolpropane triacrylate were premixed in a mass ratio of 1:10, and ball-milled at 400 rpm for 2 hours to form a graphene dispersion; the graphene dispersion was added to the premix, and high-speed sheared at 2000 rpm for 1 hour to a fineness of ≤20 μm; III. Then grind it three times with a tungsten carbide three-roll mill to make the fineness ≤5μm; then filter it through a 500-mesh filter under nitrogen pressure, and control the viscosity of the finished product to 2800-3200cps to obtain a thermosetting ink.
9. The use of dicumyl peroxide according to claim 8, characterized in that: The pigment is phthalocyanine blue BGS, and the additives include leveling agent BYK-333, defoaming agent TegoFoamex810, nano-silica and benzophenone; the roller gap pressure of the tungsten carbide three-roller machine is 0.2-0.3MPa; the trimethylolpropane triacrylate used in step I is 70-80% of its total amount; the trimethylolpropane triacrylate used in step II is 20-30% of its total amount.
10. The use of dicumyl peroxide according to claim 9, characterized in that: The mass percentage of each raw material is: epoxy acrylic resin: 35-45%; hyperbranched polyester acrylate: 10-15%; trimethylolpropane triacrylate: 12-18%; diisopropylbenzene peroxide: 3-5%; graphene nanosheets: 0.1-0.5%; phthalocyanine blue BGS: 10-12%; nano-silicon dioxide: 8-12%; Benzophenone: 1-2%; leveling agent BYK-333: 0.5-1%; defoaming agent TegoFoamex810: 0.3-0.8%; Graphene: 1.2-1.8%.
Citation Information
Patent Citations
Water-soluble environmentally-friendly gravure ink and preparation method thereof
CN102382506A
Method for synthesizing dicumyl peroxide
CN102827051A
Method for preparing titanium-based catalyst and synthesizing epoxypropane and dicumyl peroxide
CN103212437A
Dicumyl peroxide (DCP) and propylene oxied (CHPPO) coproduction method
CN104844493A
Production method for dicumyl peroxide (DCP)
CN104860861A